Response assessment by positron emission tomography‐computed tomography as compared with contrast‐enhanced computed tomography in childhood Hodgkin lymphoma can reduce the need for radiotherapy in low‐ and middle‐income countries. Issue 2 (21st November 2022) - Kalra, Manas; Bakhshi, Sameer; Singh, M.; Seth, Rachna; Verma, Nishant; Jain, Sandeep; Radhakrishnan, V.; Mandal, Piali; Mahajan, Amita; Arora, Ramandeep S.; Dinand, Veronique; Kapoor, Gauri; et al.
Abstract: Introduction: The InPOG‐HL‐15‐01, a multicentric prospective study, used a risk‐stratified and response‐based approach with doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) backbone to treat children and adolescents with newly diagnosed Hodgkin lymphoma (HL) and reduce the use of radiation therapy (RT). Children/adolescents with bulky disease or inadequate response at early response assessment (ERA) after two cycles of chemotherapy were assigned to receive RT. For ERA, positron emission tomography computed tomography (PET‐CT) was recommended but not mandatory in view of limited access. This study aimed to compare the impact of using contrast‐enhanced computed tomography (CECT) and PET‐CT on treatment decisions and outcomes. Methodology: 396 patients were enrolled and 382 had an ERA at the assigned time point. Satisfactory response was defined as Deauville score 3 or less for patients undergoing PET‐CT and complete response (CR)/very good partial response (VGPR) for patients undergoing CECT. Outcomes of interest incorporate 5 year event‐free survival (EFS), EFS including abandonment (EFSa), and overall survival (OS). Results: At ERA, satisfactory response was documented in 277 out of 382 (72.5%) participants and this was significantly higher in PET‐CT (151 out of 186, 81.2%) as compared with CECT‐based assessments (126 out of 196, 64.3%) respectively ( p value < .001). Amongst the 203 patients with nonbulky disease (wherein the indication for RT was entirely dependent on ERA), 96 out of 114 (84.2%) and 61 out of 89 (68.5%) patients achieved a satisfactory response according to the PET‐CT and CECT ( p value = .008) respectively and hence a lesser proportion of patients in the PET‐CT arm received RT. Despite a lower usage of RT the 5 year OS of both groups, ERA based on CECT (91.8%) versus PET‐CT (94.1%) was comparable ( p value = .391) and so was the 5 year EFS (86.7 vs. 85.5%, p value = .724). Conclusion: Use of PET‐CT as the modality for ERA is more likely to indicate a satisfactory response as compared with CECT and thereby decreases the need for RT in response‐based treatment algorithm for HL‐afflicted children. The reduction in the application of RT did not impact the overall outcome and plausibly would lower the risk of delayed toxic effects.